The Acquisition of Africa (1870-1914) The Nature of International Law (Volume 20/8) - van der Linden, Mieke (Brill, 2016)
Over recent decades, the responsibility for the past actions of the European colonial powers in relation to their former colonies has been subject to a lively debate. In this book, the question of the responsibility under international law of former colonial States is addressed. Such a legal responsibility would presuppose the violation of the international law that was applicable at the time of colonization. In the 'Scramble for Africa' during the Age of New Imperialism (1870-1914), European States and non-State actors mainly used cession and protectorate treaties to acquire territorial sovereignty (imperium) and property rights over land (dominium). The question is raised whether Europeans did or did not on a systematic scale breach these treaties in the context of the acquisition of territory and the expansion of empire, mainly through extending sovereignty rights and, subsequently, intervening in the internal affairs of African political entities.